Friction drilling of difficult-to-machine materials: workpiece microstructural alterations and tool wear - Dehghan, Shayan; Ismail, Mohd Idris Shah; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah (MDPI, 2019)
Difficult-to-machine materials are metals that have great toughness, high work-hardening, and low thermal conductivity. Friction drilling of difficult-to-machine materials is a technically challenging task due to the difficulty of friction drilling, leading to excessive tool wear, which adversely affects surface integrity and product performance. In the present study, the microstructural changes of workpieces and tool wear for friction drilling of AISI304, Ti-6Al-4V, and Inconel718 are characterized. It helps to have an in-depth understanding of heat generation mechanics by friction and the mechanism of the friction drilling process. The study contributes to providing an enhanced microstructural characterization of workpiece and tool conditions, which identifies the material behavior and shows how it affects the bushing formation quality and drilling tool performance. The results reveal that the abrasive wear is mostly observed in the conical region of the tool, which has maximum contact with hole-wall. Moreover, the low thermal conductivity of Ti-6Al-4V increases frictional heat generation severely, and reduces product quality and tool life subsequently.